Simplify using law of exponent of: (-7)4 ×(-7)3
Answers
Answered by
2
Answer:
= ![(-7)^{4+3} (-7)^{4+3}](https://tex.z-dn.net/?f=%28-7%29%5E%7B4%2B3%7D)
= ![(-7)^{7} (-7)^{7}](https://tex.z-dn.net/?f=%28-7%29%5E%7B7%7D)
.
.
.
__()()()()__
Step-by-step explanation:
Answered by
0
Answer:
49^7
Step-by-step explanation:
a^n x a^m = a^m+n
with this law we simplify like
-7^4 x -7^3 = (-7 x -7 )^4+3
square of negative no is always positive
hence 49^7
hope this helps
pls mark me the brainliest
Similar questions